2020
DOI: 10.3390/w12030810
|View full text |Cite
|
Sign up to set email alerts
|

Indigenous Perspectives on Water Security in Saskatchewan, Canada

Abstract: The term “water security” continues to gain traction in water resources literature with broad application to human health, water quality, and sustainability of water supply. These western science applications focus almost exclusively on the material value of water for human uses and activities. This paper offers voice to other interpretations of water security based on semi-structured interviews with Indigenous participants representing varied backgrounds and communities from Saskatchewan, a Canadian prairie p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…Our findings confirm recent research on water security within other Indigenous Nations [ 26 , 27 , 28 , 29 , 55 ]. Our study also confirmed that the impacts of water insecurity are not merely conceptualized in material physical terms but are also understood in cultural and spiritual terms [ 27 , 28 ]. For many Indigenous people, water is inherently connected to our health and well-being, requiring that research on water insecurity also consider cultural values connected to water.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Our findings confirm recent research on water security within other Indigenous Nations [ 26 , 27 , 28 , 29 , 55 ]. Our study also confirmed that the impacts of water insecurity are not merely conceptualized in material physical terms but are also understood in cultural and spiritual terms [ 27 , 28 ]. For many Indigenous people, water is inherently connected to our health and well-being, requiring that research on water insecurity also consider cultural values connected to water.…”
Section: Discussionsupporting
confidence: 92%
“…For many Indigenous people, water is inherently connected to our health and well-being, requiring that research on water insecurity also consider cultural values connected to water. Recently, researchers from Canada used in-depth interviews with tribal members to investigate the meaning of “water security” from an Indigenous perspective [ 28 ]. In their exploration they described a relationship where water provides for the people and in turn the people provide for it (reciprocity).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations